What causes the insight memory advantage? - Danek, Amory H.; Wiley, Jennifer (Cognition, 2020)
Prior research indicates that solutions accompanied by an Aha! experience are remembered better than those missing this feeling of epiphany. The question for the present studies was whether this insight memory advantage for problem solutions is modulated by the affective component of insight (the strong feelings that typically accompany the Aha! experience), or by the cognitive component (the restructuring or representational change that occurs during insightful problem solving). In both studies, participants viewed a set of magic trick videos to generate solutions for how each trick was done, and memory for the generated solutions was tested after a week delay. They also indicated the extent to which they experienced an Aha! moment at solution along with other perceptions of their experience. In the second study, they additionally rated the relevance of five action verbs for each trick (including one that implied the correct solution) multiple times during solution as a measure of restructuring the problem representation. The explanation for the insight memory advantage that was best supported by the results is that it is the joint consequence of finding correct solutions, the subjective feeling that one has found a correct solution (certainty), and experiencing an emotional pleasurable reaction during the problem solving process that all contribute to better memory for the solution. However, it did not seem to rely on having reached the solution via a sudden restructuring process.
Online veröffentlicht: 3. August 2020
Gesehen am 04.01.2021